“What do fishermen catch?”; Exploring Talk between Students in Primary Science Classroom Implementing Curriculum 2013 - Munasprianto Ramli (Faculty of Educational Sciences, Syarif Hidayatullah State Islamic University, 2018)
AbstractThe objective of this research is to explore of dialogue in primary science classrooms that implement Curriculum 2013. Dialogue is a term used in a broad sense to mean the exchange of information, thought and ideas from the sources to audiences through both written and spoken language. In this study, the sort of dialogue I am interested in is classroom talk; even more specifically, talk between students in the primary science classroom. A case study approach is employed for this study. I am focusing my study on twelve science lessons at year four of one primary schools in the Greater Jakarta. Data were gathered using classroom observations. I wrote a field note for each lesson and record the observation using audio and video recorder For analysing the data, I employed socio culture discourse analysis. The study shows that talk between students during a science lesson is adapted from both a traditional triadic pattern called Initiation, Response, Feedback (IRF) and a non-triadic pattern of Initiation, Response, Feedback, Response, Feedback (IRFRF) chain. In addition, the findings indicate that students were able to develop the four domains of scientific literacy through talks during science lessons.AbstrakTujuan dari penelitian ini adalah untuk mengeksplorasi dialog di dalam kelas sains dasar yang menerapkan Kurikulum 2013. Dialog adalah istilah yang digunakan dalam arti luas berarti pertukaran informasi, pemikiran dan ide-ide dari sumber pembicara ke lawan bicara melalui komunikasi baik lisan maupun tulisan. Dalam penelitian ini, jenis dialog yang menarik bagi peneliti adalah pembicaraan di kelas; khususnya, pembicaraan antara siswa di kelas sains tingkat Sekolah Dasar. Pendekatan studi kasus digunakan pada penelitian ini. Fokus penelitian ini adalah dua belas materi ajar mata pelajaran sains pada kelas empat dari salah satu sekolah dasar di Jabodetabek. Data penelitian ini dikumpulkan dengan menggunakan observasi kelas. Peneliti menulis catatan lapangan untuk setiap pengajaran dan merekam kegiatan pengajaran menggunakan audio dan perekam video. Untuk menganalisis data, peneliti menggunakan analisis wacana sosial budaya. Studi ini menunjukkan bahwa perbincangan antara siswa selama pelajaran sains diadaptasi dari pola triadic-tradisional yang disebut Initiation (Inisiasi), Response (Respon), dan Feedback (Timbal Balik) yang disingkat IRF dan pola non-triadic yang disebut Initiation (Inisiasi), Response (Respon), Feedback (Timbal Balik), Response (Respon), Feedback (Timbal Balik) yang disebut denga Rantai IRFRF. Selain itu, temuan menunjukkan bahwa siswa mampu mengembangkan empat domain literasi ilmiah melalui diskusi selama pelajaran ilmu pengetahuan How to Cite : Ramli, M. (2018). What do fishermen catch?”; Exploring Talk between Students in Primary Science Classroom Implementing Curriculum 2013. TARBIYA: Journal of Education in Muslim Society, 5(1), 1-10. doi:10.15408/tjems.v5i1.7496.